SIMILARITAS DEFINISI DOKUMEN PERUNDANG-UNDANGAN BERDASARKAN KAMUS BESAR BAHASA INDONESIA MENGGUNAKAN LESK ALGORITHM (Information Technology and Telematics, 2015)
Abstraction - Legislation is written law which is established by specific ways by officials who authorized and set forth in a written form. In general, information such as the definition developed in the community not only from the legislation. However, it also comes from Indonesian dictionary. Indonesian Dictionary is an Indonesian official monolingual dictionary compiled by the Agency for Development and Language Development and published by Balai Pustaka. With the two references in obtaining the information, would be more appropriate if there is a similarity systems that seek common definition is based on the search terms. This research will make the system definition document similarity legislation by a large Indonesian dictionary using lesk algorithm. Lesk algorithm is a similarity method to get the same definition (overlap) for a particular word. In the execution takes an index value to be able to calculate the amount of similarity in words, before declaring the definition of the word is the similarity. This document similarity definition systems created using the Java programming language. As for the database used is Microsoft SQL Server 2008 R2. The research produced a document legislation has the same definition with a large Indonesian dictionary definition is based on the search terms. From the research that has been done, it can be concluded that the system definition document similarity law by using a large dictionary Indonesian lesk algorithm has a success percentage of 28.6% (twenty-eight point six percent).   Keywords: Lesk algorithm, Similarity documents, legislation.